2006
DOI: 10.1002/qua.21234
|View full text |Cite
|
Sign up to set email alerts
|

First principle study of the structure of conjugated amides and thioamides

Abstract: ABSTRACT:On the basis of ab initio and density functional theory (DFT) calculations of the o-coumaric amide and thioamide, the latter is found to have better delocalization. It is demonstrated that the thioamide function features stronger attraction for electron density from the conjugated residue. Therefore, the electronic distribution in the thioamide favors stable phenoxyl radical formation. This is a reason to expect better antioxidant activity of the thioamide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…For example, spectroscopic investigations using neutron scattering as well as quantum-chemistry calculations of secondary amide derivatives have been used to understand the force field of proteins and poly amino acids . Indeed, compounds such as acetamide, , formamide, thioamide, and their derivatives served as simple models for investigating the nature of secondary amide functions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, spectroscopic investigations using neutron scattering as well as quantum-chemistry calculations of secondary amide derivatives have been used to understand the force field of proteins and poly amino acids . Indeed, compounds such as acetamide, , formamide, thioamide, and their derivatives served as simple models for investigating the nature of secondary amide functions.…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical and medicinal aspects of amides have been the subject of constant research. Vibrational spectral investigations as well as quantum chemistry calculations of secondary amide derivatives have been used to understand the force field of proteins and polyamino acids, where compounds such as acetamide, , formamide, thioamide, and their derivatives served as simple models for investigating the nature of secondary amide functions. Also along these lines, in order to understand the dynamics of individual molecular fragments and to model the dynamics of biopolymers, the compounds of the acetanilide family, Figure , have attracted enormous attention.…”
Section: Introductionmentioning
confidence: 99%
“…7,16,22,26 In addition, it was found that the degree of conjugation in thioamides is considerably higher than amides which made it as stronger p-electron attractor. 27 Nevertheless, thiosemicarbazides with thiolated BHT could convert into several radical by donating the proton to reduce DPPH radical. The possible radical formation of synthesized thiosemicarbazides can be drawn as Scheme 5.…”
Section: Antioxidant Evaluation By Dpphmentioning
confidence: 99%